Volcanic tourist destinations - Erfurt-Cooper, Patricia (Geoheritage, Geoparks and Geotourism, Conservation and Management Series, 2014)
Volcanic landscapes, both active and dormant, and their related features provide priceless natural resources which are used worldwide as sustainable tourist attractions. This comprehensive book addresses the growing interest in the geological heritage of volcanic landforms and their role in tourism. Individual chapters and case studies present a balanced view about the global volcano tourism sector and include discussions of various volcanic hazards and the potential for disasters and accidents with a main focus on safety for visitors. While some chapters concentrate predominantly on the geoscience aspects of a particular area, others emphasise the overall geodiversity of the natural and cultural heritage and its integration into various tourism sectors such as geotourism and adventure tourism as well as health tourism based on volcanic hot springs. The chapters are contributed by highly qualified internationally based scientists from various disciplines including volcanology, seismology, geology, geomorphology, geography, tourism research and experts specialising in protected site management. To raise the awareness about hazards and the potential exposure to danger in these specific natural settings, aspects of public safety, risk perception and risk management are covered in several contributions. Discussions of a number of historical events related to volcanoes as well as case studies of interesting socio-cultural settings are included to provide something of interest for every reader. Detailed descriptions of the different volcanic destinations also showcase their role in the conservation and sustainability of these unique geosites in many countries. In addition volcanic geotourism offers an unforgettable educational experience.